Teacher and student beliefs on constructivist instructional design:: A case study - Altun, Sertel; Buyukduman, F. Ilke (EDAM, 2007)
The main purpose of this research is to evaluate the effects of a constructivist instructional design on a group of students and their teacher. The sample consisted of 26 students and one teacher. The research was conducted at Istanbul Technical University, School of Foreign Languages, English preparatory Program. The instructional design based on the constructivist learning principles that is developed by the teachers together with the class teacher was applied to the sample group. The data were gathered using quantitative data collection techniques, analyzed and interpreted. The findings emphasize that, in general, constructivist instructional design has a positive effect both oil the students and the teacher. On the other hand, because most schools in Turkey have an exam-oriented system, constructivist instructional design does not appeal to some students.
Keywords: constructivism; instructional design; TEFL; teacher training; higher education; Education & Educational Research